Comprehensive Error Modeling of Four Axis Gear Machine Tool. Issue 2 (March 2021) - Huang, Zhidong; Gao, Changwei; Wang, Yiyang
Abstract: The error modeling theory is studied. The configuration of the four axis gear machine tool is analyzed. Analysis and Describe of the motion of the four axis gear machine tool are investigated. The homogeneous transformation matrix of the relative static between the adjacent typical bodies is obtained and the homogeneous transformation matrix of the relative motion between the adjacent typical bodies is clarified. The comprehensive error model of four axis gear machine tool is established. The method and the integrated error model provide a theoretical basis for the machining and error analysis of complex surfaces.